Тексты с фоностилистическими фоновариантами и их перевод ( на материале узбекского языка) - Гафуров, Б.З (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the phonographic design of phonovariants of nouns in the Uzbek language when
Keywords: noun; phonovariants; stylistic coloring; language; colloquial speech